Essence and evolution of the economic security notion - Holikov Ivan V. (Problemi Ekonomiki, 2014)
The article shows the essence and evolution of the economic security notion. It shows that the “economic security” notion is based on a number of definitions and principles of “security”. It establishes that in the result of development of the post-industrial society and complication of social and state relations, this notion was used with economic orientation. It shows that nowadays economic security is understood as the state, in which such components as financial, information, socio-economic, institutional and legal, technical and technological, intellectual and personnel, power and ecological activity are in the states of “absence of threat”, “safety”, “protection from threats”, “protection”, “reliability”, “stability”, “rest”, “independence” and “within acceptable bounds”. Moreover, there is a system of prevention or reduction of impact of threats under controlled conditions. The article shows that economic security is a dynamic component of the economy, which adapts to the needs of the time. The current stage of the state development requires taking into account specific and address specific features of the object of study (for example, branch) for ensuring economic security under conditions of appearance of negative phenomena of uncertainty and risk. The prospect of further studies is developing new systems of economic security with consideration of historical grounds and modern tendencies of development of economic relations.